Computational thinking in elementary classrooms: measuring teacher understanding of computational ideas for teaching science - Yadav, Aman; Krist, Christina; Good, Jon; Caeli, Elisa Nadire (Computer science education, 2018)
A number of efforts have focused on preparing teachers to integrate CT within secondary disciplinary subject areas; however, there is little research on how CT ideas could be embedded within elementary subjects. We designed a professional development activity for elementary teachers to embed CT within science and examined how their understanding of CT emerged over the course of PD. This paper reports results from qualitative analysis of teacher responses to vignettes and open-ended questions, which presented teaching scenarios related to CT. We found that the vignettes allow us to see shift in teachers’ thinking about CT from broad and generalized ideas to more elaborate versions of those ideas. We discuss that while vignettes provided a good method to portray changes in teacher views about CT, we need additional mechanisms to monitor how teachers conceptualize and come to integrate computational thinking into elementary schools.